NEW COPPER ORE SHOWN ON SPITSBERGEN - Yevdokimov A.N. (My University, 1990)
A new copper-ore show was found within the Devonian clastic series in the southeast of Haakon VII Land, on Mt. Sigurd, near the tectonic contact with the Upper Proterozoic metamorphic rocks of the Hekla Hook complex. The summit of the mountain is made up of a series of volcanic structures - diatremes of alkalic olivine basalts of Quaternary age. A ridge of volcanics up to 4.5 km long intersects the zone of tectonic contact of the Proterozoic with the Devonian rocks. The Proterozoic metamorphics consist of marbles, greenschists and gray granites of the General Fjell formation. The ore show fills a series of fractures branching off from the regional fault on the east, and thus constitutes a northeastward-elongated zone of hydrothermal sulfide quartz-carbonate mineralization in the calcareous horizons of the Devonian clastic rocks. The most likely source of the ore material are the Devonian clastic host deposits containing it. The main ore components are present in disseminated state in the red, gray and green sandstones lying hypsometrically below the zone of ore mineralization.
Keywords: Proterozoic; Devonian; Quaternary; Докембрий::Протерозой; Кайнозой::Четвертичная; Cenozoic::Quaternary; Paleozoic::Devonian; Precambrian::Proterozoic; Палеозой::Девонская